Double down south [videorecording (DVD)] - Schulman, Tom; Simmons, Lili, 1993-; Coates, Kim, 1958-; Rigney, Igby; Bower, Tom, 1938- (Level 33 Entertainment, 2024)
In the dangerous high-stakes world of illegal keno-pool gambling, veteran ace Nick is enamored of smart, tough, and charming newcomer Diana and is determined to stake her. Diana must prove herself in a man's world to win a match against DuBinion, the world's best shooter. Soon Diana and Nick find themselves in more danger than they ever imagined.